Flint Hills Forever Dependent On Horses - Frank J. Buchman (Symphony in the Flint Hills, 2010)
Horses have always been an essential element of the Flint Hills. Despite many changes during Chase County’s history, and continually innovative technology, horses will always be a key part of operating the world-renowned bluestem grasslands.
Keywords: Flint Hills; horses; cowboy; technology; bluestem; grassland; Bazaar; Chase County; Rock Creek Ranch; Tim Miser; livelihood; farm; ranch; cattle; Native American Indians; cattlemen; cows; Diamond Springs; Clements; crops; land; frontier; family; Hereford; Brahman; feedlot; grain; Anderson family; Emporia; Strong City; Crofoot Feedlot; rodeo; horseback; work; tradition